2007
DOI: 10.3844/ajidsp.2007.123.127
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Herpesvirus 8 Infection in Type 2 Diabetes Mellitus Patients

Abstract: In this study a possible relationship between the presence of type 2 diabetes (DM2) and the Human Herpesvirus 8 infection (HHV-8) has been evaluated. The presence of HHV-8 DNA was monitored by nested PCR and Southern blotting in peripheral blood leucocytes of DM2 patients admitted to the Diabetology and Metabolic Disease Service of the “S. Giovanni di Dio” Hospital (Cagliari, Italy); healthy blood donor subjects were examined as controls. The results suggest that the frequency of HHV-8 DNA detection is more el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 16 publications
3
13
0
Order By: Relevance
“…A) showed that 17% (19/108) of healthy donors were HHV8‐positive, confirming previous data on HHV8 general prevalence in Sardinian population [Ingianni et al, ]. By contrast, 96/168 (57%) of type 2 diabetes patients resulted infected with HHV8, confirming the high prevalence of HHV8 infection in Sardinian patients affected by type 2 diabetes [Ingianni et al, ].…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…A) showed that 17% (19/108) of healthy donors were HHV8‐positive, confirming previous data on HHV8 general prevalence in Sardinian population [Ingianni et al, ]. By contrast, 96/168 (57%) of type 2 diabetes patients resulted infected with HHV8, confirming the high prevalence of HHV8 infection in Sardinian patients affected by type 2 diabetes [Ingianni et al, ].…”
Section: Resultssupporting
confidence: 83%
“…The susceptibility to type 2 diabetes is thought to be related to both genetic and environmental factors, possibly including infection by chronic stressors for immune system such as herpesviruses. In accord with this hypothesis, we and others observed an increased frequency of human herpesvirus 8 (HHV8) infection in type 2 diabetes patients, respectively in the Sardinian population [Ingianni et al, ] and in the sub‐Saharan Africans [Sobngwi et al, ].…”
Section: Introductionsupporting
confidence: 74%
See 3 more Smart Citations